2005
DOI: 10.1159/000086752
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Identification of a Sympathetic Component in the Hypoglossal Nerve of Hamsters Using Experimental Degeneration and Horseradish Peroxidase Methods

Abstract: We employed experimental degeneration, tract-tracing with wheatgerm agglutinin conjugated with horseradish peroxidase (WGA-HRP) and electron microscopy to explore the postganglionic sympathetic fibers in the hypoglossal nerve of hamsters. Quantitative results of normal untreated animals at the electron microscopic level showed the existence of unmyelinated fibers, which made up about 20% of the total fibers in the nerve, being more numerous on the left side. The nerve fibers were preferentially distributed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 67 publications
1
2
0
1
Order By: Relevance
“…Our earlier studies on the hypoglossal nerve of hamsters found no parasympathetic component, but confirmed the presence of sympathetic fibers (Tseng et al. 2001, 2005). Interestingly, we observed that most of the sympathetic fibers in hypoglossal nerve originate from large multipolar neurons in SCG (Tseng et al.…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…Our earlier studies on the hypoglossal nerve of hamsters found no parasympathetic component, but confirmed the presence of sympathetic fibers (Tseng et al. 2001, 2005). Interestingly, we observed that most of the sympathetic fibers in hypoglossal nerve originate from large multipolar neurons in SCG (Tseng et al.…”
Section: Introductionsupporting
confidence: 75%
“…Our previous experiments in hamsters (Tseng et al. 2001, 2005) have shown that hypoglossal nerve contains postganglionic sympathetic fibers from SCG. In the present study, we provide the first evidence of a functional connection between the sympathetic component of hypoglossal nerve and posterior deep lingual glands.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…부교감신경은 역행성추적자를 이용한 연구를 통하여 아래침 분비핵(inferior salivatory nucleus)에서 기원되어 혀인두신경 (glossopharyngeal nerve)을 따라 혀로 들어와 혀 속의 신경절 을 거쳐 미각샘으로 들어가는 신경지배경로가 보고되었다 [7,9]. 반면, 미각샘에 대한 교감신경의 신경지배경로는 근래에 와서 일부 보고되었는데, 교감신경의 신경절이후신경원은 위 목신경절(superior cervical ganglion)에서 기원되어 혀밑신경 (hypoglossal nerve)을 통하여 이동하고 [16,38], 혀밑신경속의 교감신경섬유는 혀의 혈관보다는 주로 침샘에 분포하며 [34], 혀밑신경의 안쪽가지(medial branch) 만을 공유하여 턱끝혀 근과 혀의 자체근육속으로 들어간다고 하였다 [45,46]. 이상의 보고들을 종합하면, 혀의 미각샘은 혀인두신경을 통한 부교감 신경과 혀밑신경을 통한 교감신경의 신경지배에 의해 유지되 는 것은 분명하지만 각각의 신경 연결이 미각샘의 구조와 기 능에 어떤 역할을 하는지는 불분명하다.…”
Section: 서 론unclassified